Joint Press Conference on COVID-19 by IMF Managing Director and World Bank Group President - Georgieva, Kristalina (World Bank, Washington, DC, 2020)
The IMF Managing Director and the World Bank Group President held a Joint Press Conference on COVID-19. The IMF Managing Director spoke in detail about the potential direct and indirect impact of coronavirus on the global economy. She explained about how the IMF response to the epidemic will be. She told that IMF is fully committed to support the members, coordinating very closely with partner institutions. She concluded by making an important point to focus on building a bridge between where we are and that time when we would see a recovery, to make sure that the impact, in meanwhile, is softened, first and foremost, on people, and also, of course, on businesses and the economy. The World Bank Group President spoke about how the Bank is working to provide a fast, flexible response, based on developing country needs. He told them about how the Bank is providing technical assistance, goods and services that will help prevent and limit the local transmission including laboratory equipment, and systems to ensure that cases of the virus are promptly identified and traced. He mentioned about the World Bank Group and IMF working closely with WHO on the cooperation with regard to procurement and other important technical matters. He summed up by saying that the speed and breadth of the response is crucial to its effectiveness, and that's what the Bank set out to do.